DIFFERENTIAL DIAGNOSTICS OF TUBERCULOSIS AND MYCOBACTERIOSIS IN HIV PATIENTS - A. M. Panteleev; O. V. Nikulina; A. S. Khristusev; M. S. Dracheva; O. S. Sokolova; A. V. Zonova (Туберкулез и болезни лёгких)
The article analyzes the differences in clinical and laboratory manifestations of tuberculosis and mycobacteriosis in HIV patients. It was found out that mycobacteriosis developed mostly in the socially well patients at the advanced stages of HIV infection. In case of mycobacteriosis, lesions were mostly located in the abdomen with limited inflammation in the chest, while in case of tuberculosis pulmonary lesions dominated. A negative result of sputum PCR assays for tuberculosis mycobacteria with a positive result of the test for AFB is an important sign for differential diagnostics. The obtained results allow performing differential diagnostics of these diseases in those HIV infected.